The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.euf.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A Four-kallikrein Panel and β-Microseminoprotein in Predicting High-grade Prostate Cancer on Biopsy: An Independent Replication from the Finnish Section of the European Randomized Study of Screening for Prostate Cancer

Abstract: Four kallikrein markers and β-microseminoprotein in blood improve discrimination of high-grade prostate cancer at biopsy in men with elevated prostate-specific antigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…Available results about the PCA3 showed its usefulness to decide the repetition of biopsy in patients with a previous negative result, although its relationship with the aggressiveness of the tumor is controversial. On the other hand, recent diagnostic accuracy studies assessing a 4K Score and Phi showed an AUC ranging from 0.71 to 0.74 for high--grade PCa detection (24,25). Those values are similar to the ones of the AUC of [CITRATE] for csPCa detection measured in the present study (0.748).…”
Section: Discussionsupporting
confidence: 89%
“…Available results about the PCA3 showed its usefulness to decide the repetition of biopsy in patients with a previous negative result, although its relationship with the aggressiveness of the tumor is controversial. On the other hand, recent diagnostic accuracy studies assessing a 4K Score and Phi showed an AUC ranging from 0.71 to 0.74 for high--grade PCa detection (24,25). Those values are similar to the ones of the AUC of [CITRATE] for csPCa detection measured in the present study (0.748).…”
Section: Discussionsupporting
confidence: 89%
“…The controversies of using prostate-specific antigen (PSA) screening in the general population are well documented, but PSA remains the most effective PrCa biomarker currently available [10], [11], [12]. Efforts to improve sensitivity and specificity of PSA by incorporating other biological markers, such as the 4 kallikrein (4 K) marker panel [13], [14], PrCa risk calculators [15], [16], magnetic resonance imaging (MRI) [17], [18], and genetic markers [19], [20], into screening algorithms are under evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The four kallikrein marker panel was evaluated in cryopreserved samples using the AutoDelfia 1235 automatic immunoassay system (Perkin‐Elmer, Turku, Finland) in H.L.’s laboratory at Lund University, Malmö, Sweden [14–16]. The panel was also validated for precision, concordance, and accuracy using Victor instruments (Perkin‐Elmer) at all three local laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…Two USA‐based studies, the Multi‐ethnic Cohort study and the Prostate, Lung, Colorectal and Ovarian (PLCO) cancer screening trial, both reported an association between MSP and high‐grade prostate cancer on biopsy [13,14]. However, two European‐based studies found that adding MSP to the four kallikrein model increased discrimination for GG ≥2 prostate cancer either very marginally [15] or not at all [16].…”
Section: Introductionmentioning
confidence: 99%